Influence of Chloride and Nitrate Anions on Copper Electrodeposition onto Au(111) from Deep Eutectic Solvents. Issue 19 (4th August 2022) - Geng, Tanja; Schick, Benjamin W.; Uhl, Matthias; Kuehne, Alexander J. C.; Kibler, Ludwig A.; Ceblin, Maximilian U.; Jacob, Timo
Abstract: Copper electrodeposition on Au(111) from deep eutectic solvents (DESs) type III was investigated employing cyclic voltammetry as well as chronoamperometry. It was further examined on Au(poly) using the electrochemical quartz crystal microbalance (EQCM). The employed DESs are mixtures of choline chloride (ChCl) or choline nitrate (ChNO3 ) with ethylene glycol (EG) as hydrogen bond donor (HBD), each in a molar ratio of 1 : 2. CuCl, CuCl2, or Cu(NO3 )2  ⋅ 3H2 O were added as copper sources. Underpotential deposition (UPD) of Cu precedes bulk deposition in chloride as well as nitrate electrolytes. Cu deposition from Cu + in chloride media is observed as a one‐electron reaction, whereas deposition from Cu 2+ occurs in two steps since Cu + is strongly stabilized by chloride. Cu + is less stabilized by nitrate and the beginning of bulk deposition in the nitrate‐containing DES with Cu 2+ is shifted by several hundred mV to more positive potentials compared to the chloride DES. A diffusion‐controlled, three‐dimensional nucleation and growth mechanism is found by chronoamperometric measurements and analysis based on the model of Scharifker and Mostany. Abstract : Cu electrodeposition onto Au(111) is studied in deep eutectic solvents (DESs) type III with choline chloride or nitrate and ethylene glycol. Underpotential deposition is observable in all DESs. Cu + is stabilized more by Cl − than by NO3 − and with Cl − being present, the deposition involves one electron, whereas it proceeds in two consecutive steps with NO3 − . A diffusion‐controlled, three‐dimensional nucleation and growth mechanism is found.